Pelaksanaan Metode Pembelajaran Savi di Taman Kanak-Kanak Aisyiyah Bustanul Athfal Karangtengah IV Wonosari Gunungkidul - Erwin Dwi Lestari (Fakultas Agama Islam UMY, 2014)
Pelaksanaan Metode Pembelajaran Savi di Taman Kanak-Kanak Aisyiyah Bustanul Athfal Karangtengah IV Wonosari Gunungkidul